Successful pregnancy “during” pedicled transverse rectus abdominis musculocutaneous flap for breast reconstruction with normal vaginal delivery - Siew Cheng Chai; Shahlini Umayaal; Arman Zaharil Mat Saad (Indian Journal of Plastic Surgery)
A transverse rectus abdominis myocutaneous (TRAM) flap is a popular choice for breast reconstruction. Pregnancies in women following a TRAM flap present concerns regarding both safety and the integrity of the abdominal wall. We report a case of a patient who was pregnant during immediate breast reconstruction with pedicled TRAM flap and had a successful spontaneous vaginal delivery. We also conducted a literature review using PubMed on pregnancy post TRAM flap, type of reconstruction, timing of pregnancy after TRAM flap, complication, and mode of delivery, which are summarised in this report. We concluded that patients may have safe pregnancies and normal deliveries following TRAM flap breast reconstruction regardless of the time frame of pregnancy after the procedure. Therefore, TRAM flaps can continue to be a reconstruction option, even in women of childbearing age.